Myelin oligodendrocyte glycoprotein antibody-associated disease presenting as aseptic meningitis and multiple cranial neuritis: a case report - Yi-Na Zhang; Qiong Wu; Yu-Hang Dong; Ying-Jie Dai (BMC Neurology)
Abstract Both aseptic meningitis and cranial neuritis are the atypical clinical manifestations of myelin oligodendrocyte glycoprotein antibody associated disease (MOGAD), with sporadic cases of MOGAD presenting with either condition previously reported. However, no case has been documented with both of aseptic meningitis and cranial neuritis occurring concurrently. Here, we report the first such case: a 59-year-old male uniquely presenting with aseptic meningitis and multiple cranial neuritis simultaneously. Diagnosis of MOGAD was confirmed by positive MOG antibody titers in both serum and cerebrospinal fluid. Following corticosteroid treatment, the clinical symptoms, cerebrospinal fluid parameters, and imaging findings related to aseptic meningitis improved. Paradoxically, the cranial neuritis symptoms worsened. Regrettably, the patient succumbed to extreme debilitation and dysphagia ten days post-discharge. This case underscores the importance of considering MOGAD in patients presenting with concurrent aseptic meningitis and multiple cranial neuritis. Notably, compromised physical status may be a critical determinant of poor prognosis in such cases.